Evaluation Of Teaching Material Suitability With The Principles Of The Merdeka Curriculum At Public Elementary School 05 Huu - Hajar, Qurban; Masita, Masita; Pratiwi, Ayu (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The purpose of this study is to determine: (1) the planning of independent curriculum learning at SDN 05 Hu'u, (2) the implementation of independent curriculum learning at SDN 05 Hu'u, and (3) the assessment of independent curriculum learning at SDN 05 Hu'u. This research was conducted at SDN 05 Hu'u using a qualitative descriptive approach and methodology. Data were collected using interviews, observation, and documentation methods. The data analysis applied in this study includes data condensation, data presentation, and drawing conclusions. Data validity was ensured through triangulation, including source triangulation and technique triangulation. The findings of the study at SDN 05 Hu'u are as follows: (1) In learning planning, the teaching materials used by teachers align with and refer to the teaching tools provided by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), with options for self-modification.(2) The learning process conducted by teachers strives to adhere to the principles of the independent curriculum, currently in the development stage, focusing on student-centered learning and the appropriateness of the teaching methods used. (3) Assessments are carried out in accordance with the assessment principles launched by Kemendikbud.